Price Manipulation in Indonesian Capital Market: Empirical Analysis on Stockbroker’s Behavior and Interaction Pattern between Domestic Investors and Foreign Investors - Wibowo, Buddi (The Indonesian Capital Market Review, 2010)
Price manipulation in stock market transaction is an important issue when developing investor conidence and market integrity is a priority. Price manipulation is prevalent in emerging markets, which still have institutional problems and lack regulations. A stock market as a mutual company has an institutional problem when a stock broker instead of being an intermediary, behaves like a dealer and a principal for some stocks. A stock broker has strong incentives to give a signal to public investors about price of some stocks in order to get an unfair proit. A usual pattern of manipulation done by stock broker is a pump and dump manipulation. Artiicial price increase was made by manipulators through buying and selling activities among themselves until tend chaser and naive investors jump to this game. When stock price is at the highest level, manipulators start selling their stock. This research measured and identiied behavior pattern of stock brokers in Indonesian Stock Market, concerning their contribution to price manipulation existence. Because of the important role played by foreign investors in Indonesian stock market, this research would also identify interaction pattern between foreign and domestic investors. Empirical researches showed that foreign investors were underperformed domestic investors in Indonesian stock market (Dvorak, 2005, and Agarwal et al. 2009). In spite of their superior experience and inancial support compared to domestic investosr, foreign investors got lower return on average. Agarwal et al. (2009) showed this phenomenon occured because foreign investors were more aggressive than domestic investors. Dvorak (2005) argued that domestic investors had more access and network to collect short run information and were able to transfer those information to proitable trading strategy. This research tested new hypothesis about foreign investors' underperformance, that those foreign investors were entrapped in manipulative mechanism done by domestic investors having short run information through domestic stockbroker companies.